Characterization and Effect of Chitosan Concentration Variations on the Nanosuspension Formula of Ethanol Extracts from Plantago major L. Leaves Using the Ionic Gelation Method - Irawan, Muhamad Bayu; Hertiani, Triana; Martien, Ronny (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
The ethanol extract of Plantago major L. leaves contains secondary metabolites, including phenolics and iridoid glycosides, which exhibit anti-inflammatory and wound-healing properties. Nanoparticle technology, in the form of nanosuspensions, is a method that can enhance the ability of active compounds to pass through cell membranes at the nanoscale. This study aimed to characterize and investigate the effects of varying chitosan concentrations on the nanosuspension formulation of Plantago major L. ethanol leaf extract using the ionic gelation method. The ethanol extract was formulated into nanosuspensions with five different concentrations of chitosan polymer: 0.25% (F1), 0.5% (F2), 0.75% (F3), 1% (F4), and 1.25% (F5). Testing parameters included particle size, polydispersity index (PDI), and zeta potential, measured using the Malvern Zetasizer Nano ZS instrument. The characterization results for all formulations showed an average particle size ranging from 445.7 to 811.5 nm, a PDI ranging from 0.385 to 0.518, and a zeta potential between 23.9 and 31.0 mV. These results indicate that all formulations fall within the nanoparticle size range (10–1,000 nm), exhibit relatively homogeneous polydispersity indices, and display stable zeta potentials. Variations in chitosan concentration in each nanosuspension formula of ethanol extract of Plantago major L. influenced the characterization, with increasing chitosan concentration resulting in larger particle sizes and higher zeta potentials, thereby enhancing the potential for these nanosuspensions to be formulated into drug delivery systems.